ARAHAN KEBIJAKAN PENGENDALIAN KONVERSI LAHAN SAWAH DI KOTA SOLOK - Siska Nofita; Santun R.P Sitorus; Atang Sutandi (Diponegoro University, 2016)
Paddy field conversion occurs along with population growth followed by increased need for non-agricultural land. This research aims to formulate the direction control of paddy field conversion in Solok. Therefore it is necessary to analyze, they are scalogram analysis, and stepwise regression analysis. Paddy fields conversion in period of 2004-2014 in the Solok city 32,28 ha, mostly in the Lubuk Sikarah District. The threat of paddy fields conversion based of RTRW Solok city 2012-2031 is 403,60 ha (41,55%). Most of the villages in Solok belong to Hierarchy 1 except IX Korong with hierarchy 2 and Laing with hierarchy 3. The factors affecting of paddy field conversion in Solok city is land and building tax, land tittling, and the allocation of land for industrial, low density residential, high density residential, worship, and paddy fields allocation in the RTRW. Control direction of paddy field conversion in Solok city is to raise taxes on non-agriculture land, increasing the role of traditional institutions, community leaders and agricultural extension, zoning by setting RDTR of Solok city, determination of food sustainable agricultural land (LP2B) and repair damaged irrigation networks.